Pencegahan Infeksi Menular Seksual pada Perilaku Seks Multipartner Remaja di Kota Samarinda - Renatha Widyarisa Kristiono; Joko Sapto Pramono; Dian Ardyanti (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2025)
Sexually Transmitted Infections (STIs) are infections transmitted through sexual contact and can be caused by bacteria, viruses, fungi, or parasites. STIs can affect anyone and may result in serious health consequences, particularly concerning the reproductive system. Adolescents are in a developmental phase characterized by high curiosity about sexual behavior, placing them at greater risk for unsafe sexual practices. Data shows that 59% of women and 74% of men have engaged in premarital sex. This study aims to examine STI prevention efforts among adolescents with multiple sexual partners in Samarinda City. This research employed a qualitative approach using a case study design. The study involved seven informants: one key informant, four main informants, and two supporting informants. Data were collected through in-depth interviews. Research shows that adolescents have good knowledge about sexually transmitted infections (STIs) and their types, but their attitude toward prevention remains low. Most informants did not use contraceptives during sexual intercourse. Lifestyle and external factors, such as peer influence and the use of online dating apps, also contribute to multi-partner sexual behavior. Adolescents' sexual activities range from physical intimacy, such as kissing, to engaging in sexual intercourse with more than one partner. Some informants consider this behavior to be common in modern relationships. Preventive measures taken by adolescents include using contraceptives during intercourse and maintaining genital hygiene. While adolescents demonstrate sufficient knowledge about STIs, their attitudes and preventive practices need significant improvement